1992
DOI: 10.1021/jm00103a010
|View full text |Cite
|
Sign up to set email alerts
|

Bioisosteric replacement of the .alpha.-amino carboxylic acid functionality in 2-amino-5-phosphonopentanoic acid yields unique 3,4-diamino-3-cyclobutene-1,2-dione containing NMDA antagonists

Abstract: In this report, a novel bioisostere of the alpha-amino acid, 3,4-diamino-3-cyclobutene-1,2-dione, has been incorporated into a series of compounds which are NMDA antagonists. These compounds, which are achiral and easily prepared, demonstrated good affinity at the NMDA receptor by their ability to displace [3H]CPP binding in vitro. In particular, the phosphonic acid 24 provided protection against NMDA-induced lethality in mice equivalent to 2-amino-7-phosphonoheptanoic acid (5). This was considered an encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…Its chemical structure which contains an (S)-alanine moiety attached to a five-membered heterocycle was determined by chemical methods, 113,114 synthesis, 115 and X-ray crystallographic studies. 116 In binding studies at native iGluRs, QUIS has been shown to be a nonselective high affinity ligand 117 (Table VII) and furthermore in functional assays QUIS has been shown to be a full agonist. 118 Moreover, QUIS is a potent agonist at the metabotropic receptors (mGluR5: EC 50 ¼ 55 nM).…”
Section: Q U I S Q U a L I C A C I D A N D A N A L O G Smentioning
confidence: 99%
“…Its chemical structure which contains an (S)-alanine moiety attached to a five-membered heterocycle was determined by chemical methods, 113,114 synthesis, 115 and X-ray crystallographic studies. 116 In binding studies at native iGluRs, QUIS has been shown to be a nonselective high affinity ligand 117 (Table VII) and furthermore in functional assays QUIS has been shown to be a full agonist. 118 Moreover, QUIS is a potent agonist at the metabotropic receptors (mGluR5: EC 50 ¼ 55 nM).…”
Section: Q U I S Q U a L I C A C I D A N D A N A L O G Smentioning
confidence: 99%
“…For example, squaric acid and related derivatives have been successfully employed as carboxylic acid surrogates in drug design. 3-6 In similar fashion, cyclopentane-1,3-diones (Figure 1A) are effective substitutes for the carboxylic acid moiety of known thromboxane A 2 (TP) receptor antagonists ( e.g. , 1 , 7 Figure 1C), leading to potent derivatives.…”
mentioning
confidence: 89%
“…All NMDA receptors possess several binding sites of pharmacological interest including those for glutamate, glycine, polyamines and open channel blockers [129]. A novel squaryl molecular metaphor of the amino acid, 3,4-diamino-3-cyclobutene-1,2-dione, has been incorporated into a series of NMDA antagonists [130]. These achiral compounds have demonstrated an affinity for the NMDA receptor, for example perzinfotel (EAA-090).…”
Section: Kitsonmentioning
confidence: 99%
“…An alternative to the synthesis of substituted cyclobutenediones, is a free radical approach developed by the research group of Kinney [130]. This strategy is used in the presence of the diethoxyphosphinyl group required for the synthesis of potential NMDA antagonists, as well as other functionalities [132].…”
Section: Figure 35 Synthesis Of Phosphonic Acid Squaramidementioning
confidence: 99%